Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.3390/ijms19072005
|View full text |Cite
|
Sign up to set email alerts
|

DEAD-Box Protein RNA-Helicase DDX6 Regulates the Expression of HER2 and FGFR2 at the Post-Transcriptional Step in Gastric Cancer Cells

Abstract: The human DEAD/H-box RNA helicase DDX6 (RCK/p54) is a protein encoded by the fusion gene from the t(11;14)(q23;q32) chromosomal translocation observed in human B-cell lymphoma cell line RC-K8. DDX6 has a variety of functions such as translation initiation, pre-mRNA splicing, and ribosome assembly. However, details of the regulatory mechanism governing DDX6 and the functions of DDX6 are largely unknown. Previously, we reported that DDX6 is overexpressed in most malignant cell lines and clinical colorectal tumor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 34 publications
0
10
0
Order By: Relevance
“…Since HER2 was not a direct target of miR-143, we sought to elucidate the mechanism underlying the down-regulation of HER2. As we had previously reported that DDX6 post-transcriptionally regulates HER2 expression [16], we next examined the expression level of DDX6. As expected, the expression level of DDX6 was significantly decreased in MKN-7 and KATO-III cells treated with syn-miR-143 (Figure 4B).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Since HER2 was not a direct target of miR-143, we sought to elucidate the mechanism underlying the down-regulation of HER2. As we had previously reported that DDX6 post-transcriptionally regulates HER2 expression [16], we next examined the expression level of DDX6. As expected, the expression level of DDX6 was significantly decreased in MKN-7 and KATO-III cells treated with syn-miR-143 (Figure 4B).…”
Section: Resultsmentioning
confidence: 99%
“…In our previous studies, we detected the overexpression of DDX6 in most of the tumor samples and cell lines examined, and found that DDX6 positively regulates c-Myc expression at the translational step in various cancers [22,23,24]. Furthermore, DDX6 also positively regulates HER2 expression at the translation step in GC cells [16]. In the present study, we demonstrated DDX6 to be a direct target of syn-miR-143 and reconfirmed the regulatory function of DDX6 in HER2 expression (Figure 4A–D, Supplementary Figure S2).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We focused on the DEAD box protein DDX49 as one of the genes whose expression was most altered by morphine. Other members of the DEAD box family have already been implicated in cancer [ 20 ]. For example, overexpression of DDX5 (also called p68) can transform healthy cells, and it is up-regulated in colorectal cancer [ 21 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Taken together, these findings suggest that DDX6 plays an important evolutionarily conserved role in cell cycle progression and proliferation, probably through the regulation of translation of specific key mRNAs. However, another group showed that overexpression of DDX6 leads to inhibition of cell growth and a decrease in anchorage-independent growth, a hallmark of malignant transformation [ 67 ]. Since DDX6 may become a valuable target for cancer therapy [ 68 , 69 ], the significant role of this helicase in the regulation of the cell cycle should be taken into account in order to avoid secondary side effects.…”
Section: Rna Helicases In the Regulation Of Cell Cyclementioning
confidence: 99%